Reliable Service Execution Based on Probabilistic Moving Prediction in Mobile Wireless Sensor Network - Haiyang Hu; Junfeng Zhang; Hua Hu (Dianxin kexue)
By collaborating with each other，nodes in mobile wireless sensor network（MWSN）can filter，calculate and composite the data so as to provide it in forms of services to different users.However，due to the uncertain moving behavior and the limited wireless transmission，executing services in MWSN has to consider the time needed in nodes executing their services，and the physical region in which two nodes can communicate with each other by wireless channel.Probabilistic methods were used to define and predict the uncertain moving behavior of each node，and then the reliability was measured that two nodes can successfully communicate with each other under their wireless transmission range during a certain time period in the future.An approximate approach based on Monte Carlo simulation was also given to calculate nodes’ motions and the reliabilities of their successful communications.By consider the thresholds of execution time and the reliabilities of nodes’ successful communications，two algorithms were given to make the scheme of selecting nodes executing a group of services provided by the users，one using the approach of completely searching and one adopting the Pareto-dominated local k-th optimized method.Finally，experimented were conducted to evaluate our methods.